Unscripted - Bunn, T. Davis, 1952- (Revell, a division of Baker Publishing Group, 2019)
"A Hollywood producer reeling from his best friend's betrayal and an LA lawyer who has sacrificed everything for her career are drawn together to untangle a web of lies and deceit that threatens their future"--